(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The present article investigates combined effects of variable viscosity, viscous dissipation and thermal radiation on unsteady natural convection Couette flow through vertical porous channel. Non-linear Rosseland heat diffusion is deployed for the solution of the flow equations which as a consequence; together with the effects of variable viscosity, viscous dissipation and thermal radiation have resulted to high non-linear equations for the flow formation. Appropriate similarity variables are used to convert the partial differential equations associated with the fluid formation into dimensionless ordinary differential equations (ODEs) and the emerging ODEs are solved using Adomian decomposition method (ADM) and computer aided algebra package. Influences of the physical parameters involved in the problem are presented, discussed and conclusions are drawn. During the investigation; it was found that the fluid velocity and temperature were found to increase with increase in Eckert number, viscosity variation and thermal radiation.